Edible mealworms: can fermentation improve consumer acceptability and nutritional value? - Wilson, John W., author; Weir, Tiffany, advisor; Bunning, Marisa, committee member; Stull, Valerie, committee member; Nair, Mahesh, committee member (Colorado State University. Libraries, 2023)
As the global population increases, the demand for animal-based protein is also on the rise. To meet this demand, it is important to identify sustainable sources of animal protein that have a smaller environmental impact than conventional animal protein production. One potential solution to this challenge is the development of consumer-acceptable insect-based protein products utilizing the larva and pupae of Tenebrio molitor, a type of darkling beetle whose larval and pupal states are edible. These beetles can be reared in small spaces, do not require direct sources of fresh water, and convert feed into protein more efficiently than conventional meat production. In addition, their waste (frass) is dry, making it easier to contain than waste from conventional animal rearing operations, reducing the risk of contaminating the surrounding environment. In addition, the larvae and pupae can be eaten in their entirety, eliminating potential waste streams of byproducts associated with conventional meat processing. With less space, less water usage, more efficient feed conversion ratios, and nearly zero waste, the development of an edible mealworm industry in the global West would help relieve some of the pressures on the current animal protein systems and improve global food security. To accomplish this, it is necessary to generate a consistent demand in the global West for insect protein. Currently, in the United States, edible insects are largely relegated to ground powders designed to "hide" the insects or are placed in novelty products like chocolates and lollipops to confront people's notion of disgust. To introduce mealworm protein into the mainstream, it must be in a form that is accessible to the average American consumer, be safe to eat, and have comparable nutritional attributes as other protein-based products on the market. Tempeh fermentation techniques may be an appropriate approach to accomplish these goals. Tempeh fermentation uses Rhizopus oligosporus mycelium to knit together legumes into a solid cohesive substrate. The product can then be utilized in a variety of ways that are familiar to American consumers including stir frys, burgers, nuggets, and crumbles. This project seeks to utilize tempeh fermentation techniques to develop an insect-based product that is both consumer-friendly but also capitalizes on the known and emerging nutritional and environmental benefits of edible insects. In Chapter 1, I examine the safety of tempeh produced with various life stages of the Tenebrio molitor beetle. Samples were assessed for water activity (aw), and pH to determine the shelf stability of the products. Pathogenic risk was assessed through testing for coliforms, Salmonella and Listeria, and samples were analyzed for heavy meatal content via utilized Inductively Coupled Plasma and Mass Spectrometry (ICP-MS). This exploration allows us to determine best storing and cooking methods and helps identify critical control points in production to help minimize the risk to the consumer. In this chapter, I was able to demonstrate that tempeh made with Tenebrio molitor was just as safe as conventional soy-based tempeh and requires similar storage and cooking precautions to minimize the risks of consumption. In Chapter 2 we conducted a nutritional analysis of the insect-based tempeh products in comparison to traditional soy-based tempeh. We utilized ICP-MS to quantify the presence of micronutrients within each example. Samples were also analyzed for vitamins, macronutrients, and amino acid profile. We then calculated the protein digestibility using the Protein Digestibility-Corrected Amino Acid Score (PDCAAS). Comparison of results with traditional soy-tempeh products helps us to determine if the products provide comparable nutrition to products already on the market. It also helps to determine if the novel products will fill the nutritional space of more conventional sources of protein. This chapter found that the tempeh products made with the Tenebrio molitor had nutritional attributes comparable to conventional soy tempeh. Chapter 3 examines the bioavailability of iron within the sample set and compare the results to conventional bee samples, current on-the-market plant-based meat alternatives, and traditional soy-based tempeh. ICP-MS was utilized to quantify the amounts of iron present in each chemically digested sample. Then, digestates were added to Caco-2 human colonic cells to allow absorption of available iron. Iron absorption rates were then determined by using a human ferritin Eliza kit. This assessment helps us determine if the presence of insect protein improves the bioavailability of iron in a traditionally plant-based food and allows us to compare the availability of the iron in the novel products to conventional beef and current plant-based meat products. The bioavailability of iron in the novel products exceeded that of the conventional beef and the plant-based meat alternative. In Chapter 4, we conducted a consumer acceptability study to analyze the potential for consumer acceptance of a tempeh product made with 50% mealworms and 50% soybeans when compared to a commercial soy-based tempeh. An online survey was conducted to assess the public's attitudes to entomophagy, their current level of exposure to the practice, and the willingness to consume insects. Next, the mealworm soybean tempeh was evaluated by a trained sensory panel to develop a lexicon that describes the organoleptic attributes of the product. Finally, a blind in-person sensory evaluation was conducted to assess the overall acceptability of the product. During the in-person evaluation, participants were provided with different prompts to determine if details around the environmental impact of insect eating versus conventional meat production would affect the favorability of the product. Participants in this study rated the flavor equal to that of the commercial soy tempeh and majority of participants indicated they were equally or more likely to consume insect-based products again. The final chapter explores the need for research around branding and availability on insect-based food products to increase acceptance of entomophagy in Western society. This dissertation aims to determine the safety of utilizing edible insects in tempeh fermentation, examine the nutritional attributes of tempeh products made with various life stages of the Tenebrio molitor beetle, determine how effective these products are in filling their intended nutritional niches, and assess the potential for consumer acceptance of insect-based tempeh products. This dissertation provides a strong foundation for the understanding of the safety, nutrition, and acceptability of utilizing T. molitor-based tempeh as an alternative source of protein.
Keywords: nutrition; tempeh; protein; mealworm